Biliary Leak Rates After Cholecystectomy and Intraoperative Cholangiogram in Surgical Residency. Issue 5 (1st May 2015) - Shawhan, Robert R.; Porta, C. Rees; Bingham, Jason R.; McVay, Derek P.; Nelson, Daniel W.; Causey, M. Wayne; Maykel, Justin A.; Steele, Scott R.
ABSTRACT: Postoperative bile leak (BL) after cholecystectomy is a rare but dreaded complication, and is felt to be increased during surgical training. We sought to determine the incidence of BL after selective intraoperative cholangiogram (IOC) at a teaching hospital and identify risk factors for predicting BLs. A retrospective review was performed analyzing all cholecystectomy with IOCs between September 2004 and September 2011. Residents performed under staff supervision. Of 1, 799 cholecystectomies performed during the study period, only 96 (5.3%) were with IOCs (mean age 43, 65% female) and 4 BLs occurred (4.2%, 1 major duct injury, 3 cystic duct stump leaks). Univariate analysis demonstrated that male gender, significant medical comorbidities, case duration, preoperative endoscopic retrograde cholangiopancreatography, and surgery type (laparoscopic versus open) increased the patient's risk of BL; however, age, performance of secondary procedures, common bile duct exploration, resident level (PGY), and diagnosis did not increase BL risk. Multivariate regression revealed that only surgery type lead to an increased risk of BL ( p = 0.001) (OR 31.61, 95% CI 3.96–252.18). Patient factors and PGY level did not significantly affect BL rates, although open and converted procedures were associated with higher rates, suggesting an increased risk of a BL with more complex cases.